Generic realignments in Maxillariinae (Orchidaceae): Corrigenda et adenda - Blanco Coto, Mario Alberto (2008)
UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Básicas::Jardín Botánico Lankester (JBL)